THE INFLUENCE OF KNOWLEDGE MANAGEMENT, WORK ABILITY AND WORK ATTITUDE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS A MEDIATING VARIABLE - Fhifie Daryanto; Thomas Ola Langoday; Henny A Manafe (Universitas Nusa Cendana, 2026)
This study examines the influence of knowledge management, work ability, and work attitude on employee performance and job satisfaction, as well as the mediating role of job satisfaction in the relationship between these variables and employee performance at BPS NTT Province. A quantitative research design was employed, with data collected from 86 respondents through questionnaires, interviews, and observations. Data were analyzed using descriptive and inferential statistical techniques with the assistance of SmartPLS software. The findings indicate that work ability and work attitude have a significant positive effect on employee performance, whereas knowledge management does not directly influence employee performance. However, knowledge management, work ability, and work attitude each significantly affect job satisfaction. Furthermore, job satisfaction has a significant positive effect on employee performance and mediates the relationships between knowledge management, work ability, work attitude, and employee performance. These results highlight the critical role of job satisfaction in enhancing performance and underscore the importance of strengthening employees’ competencies and attitudes within public sector organizations. Keywords: Performance; Job Satisfaction; Knowledge Management; Work Ability; Work Attitude